Kinetics and Mechanism of Oxidation of Diethanolamine and Triethanolamine by Potassium Ferrate - Shan Jinhuan; Zhang Jiying (E-Journal of Chemistry)
The kinetics of oxidation of diethanolamine and triethanolamine by potassium ferrate(VI) in alkaline liquids at a constant ionic strength has been studied spectrophotometrically in the temperature range of 278.2 K-293.2 K. The reaction shows first order dependence on potassium ferrate(VI), first order dependence on each reductant, The observed rate constant (kobs) decreases with the increase in [OH-], the reaction is negative fraction order with respect to [OH-]. A plausible mechanism is proposed and the rate equations derived from the mechanism can explain all the experimental results. The rate constants of the rate-determining step and the thermodynamic activation parameters are calculated.